ANALISIS KRITERIA EKOLOGI BUDIDAYA RUMPUT LAUT DI KABUPATEN SUMBAWA BARAT - Helmy Akbar; Muhammad Arif Nasution (Universitas Teuku Umar, 2015)
West Sumbawa regency located in West Nusa Tenggara Province is potential areas for seaweed cultivation like Euchema cottonii. Currently, the center of seaweed farming activities located in the Gulf of Kertasari and Poto Tano. Market demand for commodities of E. cottonii tends to be increase, and therefore new areas of cultivation are required to be developed, through a study of physics, chemistry and biology of marine aspect is needed to assess the farming area suitability.The methodto determine the suitabilityarea is using GIS (Geographical Information System) analysis. The resultshowed thatPoto Tano District has 805 ha of suitable area for cultivation. While, Taliwang and Jereweh District consist of the area about 70 ha and 86 ha. Total land suitable for the cultivation of seaweed approximately 961 ha.